Effect of Age on Clinical Outcomes Following On-/Off-Pump Coronary Artery Bypass: Meta-Analysis and Meta-Regression - Mauldon,Hayley (2020)
Abstract Objective: There is currently much debate about which patients would benefit more after on- or off-pump coronary artery bypass grafting (CABG). The aim of this meta-analysis and meta-regression is to investigate the effect of age on short-term clinical outcomes after these approaches. Methods: To identify potential studies, systematic searches were carried out in the Excerpta Medica dataBASE (EMBASE), PubMed, Web of Science, and the Cochrane Central Register of Controlled Trials (CENTRAL). The search strategy included the key concepts of “cardiopulmonary bypass” AND “coronary artery bypass grafting” AND “off pump” OR “on pump”. This was followed by a meta-analysis and meta-regression investigating the effect of age on the incidences of stroke, myocardial infarction (MI), and mortality. Results: Thirty-seven studies including 15,324 participants were analysed. Overall, there was a significant odds reduction for patients receiving off-pump CABG suffering a stroke (odds ratio [OR] 0.770, 95% confidence intervals [CI] 0.594, 0.998, P=0.048); however, when patients were subdivided according to different age bands, this difference disappeared. There were also no significant differences in the odds of mortality (OR 0.876, 95% CI 0.703, 1.093, P=0.241) or MI (OR 0.937, 95% CI 0.795, 1.105, P=0.439). Meta-regression analysis revealed no significant relationship between age and stroke (P=0.652), age and mortality (P=548), and age and MI (P=0.464). Conclusion: Patients undergoing CABG are becoming older and may suffer from multiple comorbidities increasing their risk profile. However, with respect to short-term clinical outcomes, the patient’s age does not help in determining whether off- or on-pump is superior.